The diversity of Rab GTPases in Entamoeba histolytica - Saito-Nakano, Yumiko; Loftus, Brendan J.; Hall, Neil; Nozaki, Tomoyoshi (Experimental parasitology, 2005)
Rab proteins are ubiquitous small GTP-binding proteins that form a highly conserved family and regulate vesicular trafficking. Recent completion of the genome of the enteric protozoan parasite Entamoeba histolytica enabled us to identify an extremely large number (>90) of putative Rab genes. Multiple alignment and phylogenic analysis of amebic, human, and yeast Rab showed that only 22 amebic Rab proteins including EhRab1, EhRab2, EhRab5, EhRab7, EhRab8, EhRab11, and EhRab21 showed significant similarity to Rab from other organisms. The 69 remaining amebic Rab proteins showed only moderate similarity (<40% identity) to Rab proteins from other organisms. Approximately one-third of Rab proteins including Rab7, Rab11, and RabC form 15 subfamilies, which contain up to nine isoforms. Approximately 70% of amebic Rab genes contain single or multiple introns, and this proportion is significantly higher than that of common genes in this organism. Twenty-five Rabs possess an atypical carboxyl terminus such as CXXX, XCXX, XXCX, XXXC, and no cysteine. We propose annotation of amebic Rab genes and discuss biological significance of this extraordinary diversity of EhRab proteins in this organism.